Karakteristik Batuan Induk dan Pemodelan Cekungan di Lapangan North Aman, Cekungan Sumatra Tengah - Abdullah Azam; Asep Heri Patria K; Pongga Dikdya W; Ahmad Kurniawan P (BBPMGB LEMIGAS, 2025)
The Central Sumatra Basin is a back-arc basin and has the hottest geothermal gradient in Indonesia. Hydrocarbon production in this basin began in the 19th century and continues to this day with active production fields and exploration activities. This study aims to analyze the characteristics of the source rock, reconstruct the basin's evolution, and estimate the timing of hydrocarbon generation and expulsion at the North Aman Field in the Central Sumatra Basin. Data from two wells were used, including formation thickness, TOC, Tmax, HI, OI, Rock Eval Pyrolysis, and vitrinite reflectance. The analysis results show that Well NA-1 has source rock quality ranging from poor to excellent, with maturity levels reaching mature (Tmax 426–457°C; Ro 0.64–1.01), while NA-2 ranged from poor to very good and reached post-mature maturity levels (Tmax 406–543 °C; Ro 0.42–1.15). Both wells fall into Kerogen Type II–III, with some Type IV samples. Based on 1D basin modeling, kerogen conversion to hydrocarbons in Well NA-1 began during the Oligocene (32.26 million years ago) and underwent expulsion during the Pleistocene (0.48 million years ago), while in Well NA-2, it began during the Oligocene (32.14 million years ago) and underwent expulsion during the Pleistocene (0.89 million years ago). Overall, the source rocks in Wells NA-1 and NA-2 show potential for producing commercial hydrocarbons.